The Effect of Using Film-Based Learning Media on Increasing Student Interest in Learning in Tamalate Makassar - Buti, Walde Nai; Ansyah, Anwar (Cahaya Ilmu Cendekia Publisher, 2024)
Purpose of the study: This research aims to address the low student learning outcomes and motivation in the history learning subjects of class XII students at vocational school Tamalatea Makassar by using film media as teaching material and examining its effectiveness in enhancing the student learning achievement and interest. Methodology: This research uses a quantitative method with a population of all class XII students at Tamalatea vocational High School and a sample of 25 students. The data collection techniques are observation, questionnaires and documentation methods. The data analysis technique uses descriptive inferential statistical techniques and qualitative descriptive methods. Main Findings: The research data shows that using film media as teaching material can improve the history subject grades of class XII students at vocational school Tamalatea Makassar. The average score increases from 29.88 with a standard deviation of 6.948 to 84.40 with a standard deviation of 6.481 after using film media, exceeding the expected outcome of 75%. Novelty/Originality of this study: Used film media as teaching material in the history learning subjects of class XII students at vocational school Tamalatea Makassar, which may have different characteristics and needs from other students in other regions or countries. The research also contributes to the existing knowledge in the field of history education and media education, by showing the positive influence of film media on the student learning outcomes and motivation. The research has implications for the improvement of the history curriculum and the teacher training program in vocational schools.